Development Of A High Pressure Chamber For Spray Vessels - Amirruddin, Abdul Kadir; Mohd Razali, Hanipah (2010)
The analysis of gasoline-ethanol blends sprays in engine-like conditions is of fundamental importance for the study and development of engines. The development of spray characteristics concepts requires an efficient investigation and improvement of the applied systems. For a correct understanding of the processes inside the combustion chamber of an internal combustion engine, especially for smaller sizes of engines, a system is necessary which allows a fast adaptation to the desired parameters and an efficient conduction of the experiments. For this purpose, a High Pressure Chamber(HPC) in a 1:1 scale for small-bore engines (piston displacement approximately 76 mm) with a variable optical access (6 windows) has been developed. A high pressure chamber (HPC) has been designed for the purpose of spray characteristics studies at elevated pressures. The present HPC is designed as a versatile tool and includes the features of a well-defined core region, fast pressurize, ability to vary pressure and clearance, optical accessibility, and capability for specie measurement.